SISTEM INFORMASI PELAYANAN PUBLIK DIKECAMATAN KAMPAR TIMUR KABUPATEN KAMPAR - aguswan, aguswan (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2017)
The public information service system, hereinafter referred to as the information system, is a series of activities that include the storage and management of information and mechanisms of delivering information from the organizers to the public and vice versa in the form of oral, latin, written in Braille, image language and / or local languages , And presented manually or electronically. In order to provide information support to the implementation of public services should be held information system that is National. To that end, the organizer is obliged to manage information system which includes: Operator Profile, Executor Profile, Service Standard, Service Notification, Grievance Management and Performance Assessment.The results of the research were conducted in Kampar Timur sub-district office that highlighted the application of public service information system, where the research result stated that the availability of service information system is still incomplete, as many as 14 (40,00) respondents gave their responses, as well as respondents who responded The implementation of information service system that is as much as 12 (34,00) respondents gave their responses, and respondents who gave enough response about the implementation of service information system that is 9 (26,00) respondents who gave the response.Selanjutnya in the implementation of service information system that has been held By Kampar Timur sub-district government, the presence of inhibiting factors is the provision of non-electronic data is still incomplete, tools and technology is still limited and human resources employees who are still less professional in carrying out tasks and His responsibility in carrying out the service to the community